Determinants of household food security and maternal dietary diversity in rural Gedeo zone, southern Ethiopia: results from a cross-sectional study - Jisso, Meskerem; Biadgilign, Sibhatu; Tareke, Amare Abera; Tesfaye, Tizalegn; Zerfu, Tadesse Alemu (Frontiers in Nutrition, 2025)
BackgroundIn Ethiopia, food insecurity and poor dietary diversity continue to affect maternal and child health, particularly in rural regions.ObjectiveWe examined the status and determinants of household food security and maternal dietary diversity in rural Gedeo zone, southern Ethiopia.MethodsA cross-sectional study was conducted among randomly selected 422 households, and household food insecurity and women’s dietary diversity was measured. We conducted bivariable and multivariable logistic regression.ResultsIn this study, 65.5% of mothers (95% CI: 60.7–70.0%) and 27.9% (95% CI: 23.7–32.5%) of households had adequate dietary diversity and food security, respectively. Severe or moderate food insecurity predispose to inadequate dietary diversity, whereas, higher wealth status increased the odds of adequate dietary diversity. Maternal education increased the odds of adequate dietary diversity. Regarding household food insecurity, the size of the household having a member of 5–7 and 8–12 were 78 and 76% less likely to be food insecure among households compared to 1–4 members size [OR = 0.22 (95%CI: 0.07, 0.70)] and [OR = 0.24 (95% CI: 0.07, 0.83)] respectively. Those household having high in women’s dietary diversity were 83% less likely to have to food insecure among households compared to the lowest women’s dietary diversity [AOR = 0.17 (95% CI: 0.10, 0.31)].ConclusionHousehold wealth status, maternal education, household food security status, pregnancy status were factors affected maternal dietary diversity. Family size and dietary diversity affected household food security status. Interventions should focus on maternal literacy, empowering women on income, assuring food security to increase maternal dietary diversity.